2021
DOI: 10.1093/jxb/eraa571
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics of developing pea seeds reveals a complex antioxidant network underlying the response to sulfur deficiency and water stress

Abstract: Pea is a legume crop producing protein-rich seeds and is increasingly in demand for human consumption and animal feed. The aim of this study was to explore the proteome of developing pea seeds at three key stages covering embryogenesis, the transition to seed-filling, and the beginning of storage-protein synthesis, and to investigate how the proteome was influenced by S deficiency and water stress, applied either separately or combined. Of the 3184 proteins quantified by shotgun proteomics, 2473 accumulated at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 90 publications
0
14
0
Order By: Relevance
“…The study of sunflower seeds by transmission electron microscopy has shown that low density of the mitochondrial matrix, absence of a discontinuous outer membrane, and few cristae are associated with low ATP production through oxidative phosphorylation ( Czarna et al, 2016 ). In other crops, such as rice ( Taylor et al, 2010 ), maize ( Bahaji et al, 2019 ), and peas ( Henriet et al, 2021 ), the presence of mature mitochondria with large numbers of continuous cristae structures, an electron dense matrix, and abundant electron transport chain components were suggestive of high protein contents that enable the seed to produce large amounts of ATP through increased metabolic activity and respiration. Isolated promitochondria from rice seeds were rich in proteins but were unable to be metabolically active without imbibition.…”
Section: Mitochondria Are Indispensable For Seed Germinationmentioning
confidence: 99%
“…The study of sunflower seeds by transmission electron microscopy has shown that low density of the mitochondrial matrix, absence of a discontinuous outer membrane, and few cristae are associated with low ATP production through oxidative phosphorylation ( Czarna et al, 2016 ). In other crops, such as rice ( Taylor et al, 2010 ), maize ( Bahaji et al, 2019 ), and peas ( Henriet et al, 2021 ), the presence of mature mitochondria with large numbers of continuous cristae structures, an electron dense matrix, and abundant electron transport chain components were suggestive of high protein contents that enable the seed to produce large amounts of ATP through increased metabolic activity and respiration. Isolated promitochondria from rice seeds were rich in proteins but were unable to be metabolically active without imbibition.…”
Section: Mitochondria Are Indispensable For Seed Germinationmentioning
confidence: 99%
“…The purple area delimits selected hub genes (gene significance < -0.9 and module membership > 0.9). In B and C, homologs of OAS cluster genes and genes encoding proteins that were up-regulated in pea seeds under S- and WD/S- in Henriet et al (2021) are highlighted with black and green border lines, respectively. D, Predicted regulators of genes belonging to module M16.…”
Section: Resultsmentioning
confidence: 99%
“…To further dissect the molecular pathways activated under WD and S-, we used a multi-omics approach focusing on pea leaves. Transcriptomics, proteomics and ionomics data were obtained at different time points during stresses applied individually or in combination, on leaf samples collected from the experiment described in Henriet et al (2019, 2021). A highly specific module of genes responding to S- (occurring alone or in combination with WD) was revealed, with known and putative new regulators of the plant’s responses to this stress.…”
Section: Introductionmentioning
confidence: 99%
“…Such phenomenon also occurred in other abiotic stresses such as salt, chilling and heavy metals [21][22][23][24]. Moreover, large-scale proteomic analysis has been widely used in many other plant research as a promising tool for protein identification and gene function characterization [25,26].…”
Section: Introductionmentioning
confidence: 99%